CASP9 germline mutation in a family with multiple brain tumors - Ronellenfitsch, Michael Wilfried; Steinbach, Joachim Peter; Felsberg, Jörg; Capper, David; Schittenhelm, Jens Florian; Klink, Barbara; Mittelbronn, Michel Guy André (Brain pathology, 2017)
Abstract We report a novel CASP9 germline mutation that may increase susceptibility to the development of brain tumors. We identified this mutation in a family in which three brain tumors had developed within three generations, including two anaplastic astrocytomas occurring in cousins. The cousins were diagnosed at similar ages (29 and 31 years), and their tumors showed similar histological features. Genetic analysis revealed somatic IDH1 and TP53 mutations in both tumors. However, no germline TP53 mutations were detected, despite the fact that this family fulfills the criteria of Li?Fraumeni?like syndrome. Whole exome sequencing revealed a germline stop?gain mutation (R65X) in the CASP9 gene, which encodes caspase?9, a key molecule for the p53?dependent mitochondrial death pathway. This mutation was also detected in DNA extracted from blood samples from the two siblings who were each a parent of one of the affected cousins. Caspase?9 immunohistochemistry showed the absence of caspase?9 immunoreactivity in the anaplastic astrocytomas and normal brain tissues of the cousins. These observations suggest that CASP9 germline mutations may have played a role at least in part to the susceptibility of development of gliomas in this Li?Fraumeni?like family lacking a TP53 germline mutation.